Three-dimensional communicated porous piezoelectric ceramic and preparation method and application thereof
Based on the piezoelectric solid solution PZNNT, the three-dimensional connected porous piezoelectric ceramics are prepared by foam injection method, which solves the problem of poor stress transfer efficiency of existing porous ceramics, and achieves high energy output and excellent sensing sensitivity.
Patent Information
- Application Number
- CN202510095763.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing porous piezoelectric ceramics have poor stress transmission efficiency and poor polarization efficiency due to the discontinuity of the piezoelectric phase or the porous phase, which causes the porous ceramic d33 to drop sharply and the energy output capacity is limited.
Three-dimensional connected porous piezoelectric ceramics were prepared by foam injection method. Porous piezoelectric ceramics with high porosity and high strength were obtained by combining gel injection molding and direct foaming method.
The three-dimensional interconnection of the ceramic phase and the air phase is realized, the piezoelectric charge transfer efficiency and polarization efficiency are improved, the piezoelectric voltage constant and energy acquisition factor are significantly improved, the deterioration of d33 is alleviated, the stress transfer efficiency is enhanced, and the energy output capability and sensing sensitivity are excellent.
Smart Images

Figure CN119874405A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to a three-dimensional interconnected porous piezoelectric ceramic and a preparation method and application thereof. Background Art
[0002] Energy harvesting technology based on lead zirconate titanate (PZT) piezoelectric materials has achieved self-powering of miniaturized electronic devices and wireless sensors, and has important applications in health, environmental monitoring, intelligent positioning, underwater vehicles, and aerospace. The energy harvesting factor FOM characterizes the efficiency of piezoelectric energy harvesting. 33 , FOM 33 =d 33 ·g 33 , where d 33 is the piezoelectric charge constant, g 33 is the piezoelectric voltage constant (g 33 =d 33 / ε r ·ε0,ε r is the relative dielectric constant in the -33 direction, and ε0 is the dielectric constant of vacuum). However, the intrinsic properties of piezoelectric materials determine that d 33 and ε r The strong coupling between the two is proportional, which makes it extremely difficult to improve the energy output sensitivity and performance of piezoelectric materials. Researchers have conducted a lot of research on the optimization of piezoelectric energy harvesting performance. Material component design, single crystal preparation and texture engineering are the most common optimization methods. However, the optimization effect of the above methods is limited.
[0003] In recent years, as an alternative method, researchers have used air with a low relative dielectric constant (ε r ≈1) as a second phase introduced into piezoelectric ceramics to prepare porous piezoelectric ceramics. At present, the common porous piezoelectric ceramics have poor stress transfer efficiency and polarization efficiency due to the discontinuity of the piezoelectric phase or pore phase, which makes the porous ceramics d 33 It drops sharply and the energy output capacity is limited. Summary of the invention
[0004] The purpose of the present invention is to provide a three-dimensional interconnected porous piezoelectric ceramic and a preparation method and application thereof. The three-dimensional interconnected porous piezoelectric ceramic provided by the present invention has excellent energy output capacity.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a three-dimensional interconnected porous piezoelectric ceramic, the chemical composition of which is 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3, density is 0.52~1.43g / cm 3 The total porosity is 81.7-93.3%, the open porosity is 79.4-91.6%, the pore size is 10-300 μm, and the average pore size is 78.7-93.2 μm.
[0007] Preferably, the pore structure of the three-dimensional interconnected porous piezoelectric ceramic is spherical.
[0008] Preferably, the piezoelectric charge constant d of the three-dimensional interconnected porous piezoelectric ceramic is 33 The dielectric constant ε is 400~480pC / N at 1kHz r is 120~140, the piezoelectric voltage constant g 33 376×10 -3 ~387×10 -3 Vm / N, energy harvesting factor FOM 33 151×10 -3 ~186×10 -12 m 2 / N, peak output voltage V pp The detection voltage is 110~200V, and the detection sensitivity is 25~40V / kPa.
[0009] The present invention also provides a method for preparing the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme, comprising the following steps:
[0010] 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 ) After the O3 ceramic slurry, plasticizer, gelling agent and foaming agent are heated and mixed, they are cooled and solidified, freeze-dried, debinded and sintered in sequence to obtain the three-dimensional interconnected porous piezoelectric ceramic.
[0011] Preferably, the 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3)O3 ceramic slurry contains PZNNT ceramic powder, the mass ratio of the PZNNT ceramic powder to the plasticizer is 100:3-5; the mass ratio of the PZNNT ceramic powder to the gelling agent is 100:5-8; the mass ratio of the PZNNT ceramic powder to the foaming agent is 100:0.2-1.2.
[0012] Preferably, the cooling and curing includes cooling and heat preservation, the cooling rate is 2-5°C / min, the final temperature is 25-35°C, and the heat preservation time of the final temperature is 12-36h.
[0013] Preferably, the debinding is performed by gradient heating; the debinding by gradient heating comprises sequentially performing a first heating, a first heat preservation debinding, a second heating, a second heat preservation debinding, a third heating and a third heat preservation debinding.
[0014] Preferably, the first heating rate is 0.2-0.5°C / min; the first insulation debinding temperature is 150-250°C, and the insulation debinding time is 1-2h; the second heating rate is 0.2-0.5°C / min; the second insulation debinding temperature is 450-550°C, and the insulation debinding time is 1-2h; the third heating rate is 0.2-0.5°C / min; the third insulation debinding temperature is 600-700°C, and the insulation debinding time is 2-4h.
[0015] Preferably, the sintering temperature is 1200-1300° C., and the sintering time is 2-4 hours.
[0016] The present invention also provides the use of the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme or the three-dimensional interconnected porous piezoelectric ceramics obtained by the preparation method described in the above scheme in a piezoelectric energy harvester.
[0017] The present invention provides a three-dimensional interconnected porous piezoelectric ceramic. The three-dimensional interconnected porous piezoelectric ceramic provided by the present invention has a three-dimensional interconnected pore structure, and the ceramic phase and the air phase are three-dimensionally interconnected. Compared with traditional piezoelectric ceramics, it has a lower density and dielectric constant, and at the same time has a higher porosity and piezoelectric charge constant. On the basis of successfully decoupling the dielectric constant and the piezoelectric constant, a large amount of space charge can be simultaneously gathered at the heterogeneous interface between the ceramic phase and the air phase, and a local built-in electric field can be formed, thereby enhancing the charge transfer efficiency, improving the piezoelectric polarization efficiency, and greatly improving the piezoelectric voltage constant and energy collection factor, thereby alleviating the d 33 deterioration, excellent energy output capacity and sensing sensitivity, while also enhancing stress transfer efficiency.
[0018] The present invention also provides a method for preparing the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme. The present invention uses a piezoelectric solid solution (lead zirconate titanate-lead zinc niobate-lead nickel niobate, PZT-PZN-PNN, abbreviated as PZNNT) located near the quasi-morphous phase boundary as the basic material, and adopts a foam injection method to prepare a three-dimensional interconnected porous piezoelectric ceramic. This method is equivalent to combining the gel injection molding method with the direct foaming method. The obtained porous piezoelectric ceramics not only have high porosity and high strength, but also improve the piezoelectric properties and energy collection performance of the three-dimensional interconnected porous piezoelectric ceramics, and are environmentally friendly and low in toxicity.
[0019] The present invention also provides the use of the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme or the three-dimensional interconnected porous piezoelectric ceramics obtained by the preparation method described in the above scheme in a piezoelectric energy harvester. The three-dimensional interconnected porous piezoelectric ceramics provided by the present invention have excellent energy output capacity, are suitable for use in piezoelectric energy harvesters, and have application prospects as porous piezoelectric ceramic materials for piezoelectric energy harvesting. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 XRD patterns of the three-dimensional interconnected porous piezoelectric ceramics prepared in Examples 1 to 6;
[0022] Figure 2 The density and porosity curves of the three-dimensional interconnected porous piezoelectric ceramics prepared in Examples 1 to 6;
[0023] Figure 3 The SEM images of the three-dimensional interconnected porous piezoelectric ceramics prepared in Examples 1 to 6;
[0024] Figure 4 The electrical properties (piezoelectric voltage constant d 33 and dielectric constant ε r )curve;
[0025] Figure 5 The piezoelectric energy harvesting performance (piezoelectric voltage constant g) of the three-dimensional interconnected porous piezoelectric ceramics prepared in Examples 1 to 6 33 and piezoelectric energy harvesting factor FOM 33 )curve;
[0026] Figure 6The output electrical properties (peak output voltage V pp and detection sensitivity S) curve;
[0027] Figure numbers: a is the three-dimensional interconnected porous piezoelectric ceramic of Example 1, b is the three-dimensional interconnected porous piezoelectric ceramic of Example 2, c is the three-dimensional interconnected porous piezoelectric ceramic of Example 3, d is the three-dimensional interconnected porous piezoelectric ceramic of Example 4, e is the three-dimensional interconnected porous piezoelectric ceramic of Example 5, and f is the three-dimensional interconnected porous piezoelectric ceramic of Example 6. DETAILED DESCRIPTION
[0028] The present invention provides a three-dimensional interconnected porous piezoelectric ceramic, the chemical composition of which is 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3, density is 0.52~1.43g / cm 3 The total porosity is 81.7-93.3%, the open porosity (the proportion of the three-dimensional interconnected porous piezoelectric ceramics) is 79.4-91.6%, the pore size is 10-300 μm, and the average pore size is 78.7-93.2 μm.
[0029] In the present invention, the pore structure of the three-dimensional interconnected porous piezoelectric ceramic is preferably spherical.
[0030] The three-dimensional interconnected porous piezoelectric ceramic provided by the present invention has a piezoelectric charge constant d 33 The dielectric constant ε is 400~480pC / N at 1kHz r is 120~140, the piezoelectric voltage constant g 33 376×10 -3 ~387×10 -3 Vm / N, energy harvesting factor FOM 33 151×10 -3 ~186×10 -12 m 2 / N, peak output voltage V pp The voltage is 110-200V, and the detection sensitivity is 25-40V / kPa, which meets the performance requirements of piezoelectric energy harvester materials.
[0031] The present invention also provides a method for preparing the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme, comprising the following steps:
[0032] 0.83Pb(Zr 1 / 2 Ti 1 / 2)O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 ) After the O3 ceramic slurry, plasticizer, gelling agent and foaming agent are heated and mixed, they are cooled and solidified, freeze-dried, debinded and sintered in sequence to obtain the three-dimensional interconnected porous piezoelectric ceramic.
[0033] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0034] The present invention converts 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3 ceramic slurry, plasticizer, gelling agent and foaming agent are heated and mixed to obtain foam slurry. In the present invention, the 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 ) The preferred method for preparing the O3 ceramic slurry is: mixing the PZNNT ceramic powder, the dispersant and water (referred to as the second mixing).
[0035] In the present invention, the preparation method of the PZNNT ceramic powder is preferably: PbO, ZrO2, TiO2, ZnO, NiO and Nb2O5 are mixed (referred to as the first mixing) according to the chemical mass ratio of the chemical formula of the PZNNT ceramic powder and then calcined.
[0036] In the present invention, the first mixing is preferably grinding mixing; the grinding mixing is preferably ball milling mixing; the ball milling mixing is preferably wet ball milling mixing; the reagent used for the wet ball milling mixing is preferably ethanol; the rotation speed of the ball milling mixing is preferably 250-350rpm, specifically 300rpm; the time of the first mixing is preferably 12-36h, specifically 24h.
[0037] In the present invention, after the first mixing, the product is preferably dried; the drying temperature is preferably 50 to 70° C., and the heat preservation and drying time is preferably 8 to 20 hours. The present invention removes the reagents added by wet ball milling by drying.
[0038] In the present invention, the calcination temperature is preferably 900-1100° C., and the calcination time is preferably 0.5-2.5 h.
[0039] In the present invention, the dispersant is preferably an ammonium salt; the ammonium salt preferably includes one or both of sodium ammonium polyacrylate and triammonium citrate.
[0040] In the present invention, the mass ratio of the PZNNT ceramic powder to the dispersant is preferably 100:0.3-0.5, specifically 100:0.3, 100:0.32, 100:0.35, 100:0.37, 100:0.4, 100:0.42, 100:0.45, 100:0.47 or 100:0.5.
[0041] In the present invention, the water is preferably deionized water.
[0042] In the present invention, the mass ratio of the PZNNT ceramic powder to water is preferably 50-65:35-50, and specifically can be 50:35, 52:35, 55:35, 57:35, 60:35, 65:35, 50:40, 52:40, 55:40, 57:40, 60:40, 65:40, 50:43, 52:43, 55:35 :43, 57:43, 60:43, 65:43, 50:45, 52:45, 55:45, 57:45, 60:45, 65:45, 50:48, 52:48, 55:48, 57:48, 60:48, 65:48, 50:50, 52:50, 55:50, 57:50, 60:50, 65:50.
[0043] In the present invention, the second mixing is preferably ball milling mixing; the rotation speed of the ball milling mixing is preferably 250-350rpm, specifically 300rpm, and the ball milling time is preferably 1-3h, specifically 2h; the grinding balls used for the ball milling mixing are preferably zirconia grinding balls; the mass ratio of the grinding balls to the PZNNT ceramic powder is preferably 0.5-2:1-2.5, specifically 0.5:1, 1:1, 1.5:1, 2:1, 0.5:1.5, 1:1.5, 1.5:1.5, 2:1.5, 0.5:2, 1:2, 1.5:2, 2:2, 0.5:2.5, 1:2.5, 1.5:2.5 or 2:2.5.
[0044] In the present invention, the plasticizer is preferably a polyol; the polyol preferably includes one or more of polypropylene glycol, polyethylene glycol and polybutylene glycol.
[0045] In the present invention, the mass ratio of the PZNNT ceramic powder to the plasticizer is preferably 100:3-5, specifically 100:3, 100:3.2, 100:3.5, 100:3.7, 100:4, 100:4.2, 100:4.5, 100:4.7 or 100:5.
[0046] In the present invention, the gelling agent is preferably one or more of agar, gelatin and gum arabic. The present invention improves the curing effect of the foam slurry and the strength of the porous piezoelectric ceramic body by adding the gelling agent, and the obtained porous ceramic can have both high porosity and strength.
[0047] In the present invention, the mass ratio of the PZNNT ceramic powder to the gelling agent is preferably 100:5-8, specifically 100:5, 100:5.5, 100:6, 100:6.5, 100:7, 100:7.5 or 100:8.
[0048] In the present invention, the foaming agent is preferably an anionic foaming agent; the anionic foaming agent preferably includes one or both of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate. In the present invention, the foaming agent is added to stir and foam.
[0049] In the present invention, the mass ratio of the PZNNT ceramic powder to the foaming agent is preferably 100:0.2-1.2, specifically 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.1 or 100:1.2.
[0050] In the present invention, the temperature of the heating and mixing is preferably 40-60°C, specifically 50°C; the heating and mixing is preferably stirring and mixing in a water bath; the stirring and mixing is preferably mechanical stirring; the mechanical stirring is preferably accelerated mechanical stirring; the accelerated mechanical stirring is preferably: stirring at 400-600 rpm for 5-10 min, 700-900 rpm for 5-10 min, 1100-1500 rpm for 5-10 min, and 1800-2000 rpm for 20-30 min. The present invention performs a foaming treatment on the ceramic slurry by heating and mixing.
[0051] After obtaining the foam slurry, the present invention sequentially cools and solidifies the foam slurry and freeze-dries it to obtain a porous piezoelectric ceramic body. In the present invention, the cooling and solidification is preferably carried out in a mold; the cooling and solidification includes cooling and heat preservation, the cooling rate is preferably 2 to 5°C / min, specifically 3°C / min, the final temperature is preferably 25 to 35°C, specifically 30°C, and the heat preservation time of the final temperature is preferably 12 to 36h, specifically 24h.
[0052] In the present invention, the freeze drying temperature is preferably -70 to -40°C, specifically -60°C, and the heat preservation and drying time is preferably 12 to 24 hours, specifically 15 hours, 18 hours or 21 hours. The present invention removes water molecules through freeze drying, dries and demoulds, obtains a ceramic body with a complete structure, and can still maintain a porous skeleton structure after debinding, thereby obtaining a porous piezoelectric ceramic with a micron-scale pore structure.
[0053] After obtaining the porous piezoelectric ceramic body, the present invention sequentially performs debinding and sintering on the porous piezoelectric ceramic body to obtain the three-dimensional interconnected porous piezoelectric ceramic. In the present invention, the debinding is preferably performed by gradient heating debinding; the gradient heating debinding preferably includes sequentially performing first heating, first heat preservation debinding, second heating, second heat preservation debinding, third heating, and third heat preservation debinding.
[0054] In the present invention, the first heating rate is preferably 0.2-0.5°C / min, specifically 0.3°C / min or 0.4°C / min; the first insulation debinding temperature is preferably 150-250°C, specifically 180°C, 200°C or 220°C; the insulation debinding time is preferably 1-2h, specifically 1.5h.
[0055] In the present invention, the second heating rate is preferably 0.2-0.5°C / min, specifically 0.3°C / min or 0.4°C / min; the second insulation debinding temperature is preferably 450-550°C, specifically 470°C, 500°C or 520°C, and the insulation debinding time is preferably 1-2h, specifically 1.5h.
[0056] In the present invention, the third heating rate is preferably 0.2-0.5°C / min, specifically 0.3°C / min or 0.4°C / min; the third insulation debinding temperature is preferably 600-700°C, specifically 620°C, 650°C or 680°C, and the insulation debinding time is preferably 2-4h, specifically 3h.
[0057] In the present invention, the sintering temperature is preferably 1200-1300°C, specifically 1200°C, 1220°C, 1240°C, 1260°C, 1280°C or 1300°C, and the heat preservation sintering time is preferably 2-4h, specifically 2.5h, 3h or 3.5h. The bonding between the powders after debinding is very fragile, and it is not a porous ceramic. Sintering allows the powder particles to merge and grow together under high temperature drive, forming a strong bonding force, and then obtaining a porous ceramic.
[0058] The present invention also provides the use of the three-dimensional interconnected porous piezoelectric ceramics described in the above scheme or the three-dimensional interconnected porous piezoelectric ceramics obtained by the preparation method described in the above scheme in a piezoelectric energy harvester.
[0059] The three-dimensional interconnected porous piezoelectric ceramic provided by the present invention has excellent energy output capability, is suitable for use in piezoelectric energy harvesters, and has application prospects as a porous piezoelectric ceramic material for piezoelectric energy harvesting.
[0060] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0061] In a specific embodiment of the present invention, according to the chemical formula of the three-dimensional interconnected porous piezoelectric ceramic, 0.83Pb(Zr 1 / 2Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3, weigh PbO, ZrO2, TiO2, ZnO, NiO and Nb2O5 powders, add ethanol and mix by ball milling at 300 rpm for 24 h to obtain a mixed raw material, dry it at 60°C for 12 h to remove ethanol, calcine the dried mixed raw material at 1000°C for 1 h to obtain PZNNT ceramic powder; other reagents and materials, unless otherwise specified, are commercially available products.
[0062] Example
[0063] Embodiment A method for preparing a three-dimensional interconnected porous piezoelectric ceramic comprises the following steps:
[0064] (1) According to Table 1, weigh PZNNT ceramic powder, deionized water and dispersant triammonium citrate and place them in a ball mill, and ball mill them at 300 rpm for 2 h to obtain a ceramic slurry; pour the above ceramic slurry into a beaker and place it in a 50°C water bath, add plasticizer polyethylene glycol, gelling agent gelatin and foaming agent sodium dodecyl sulfate, stir at 500 rpm for 8 min, 800 rpm for 8 min, 1200 rpm for 8 min, and 2000 rpm for 25 min to obtain a stable foam slurry.
[0065] Table 1 Raw material dosage of Examples 1 to 6
[0066]
[0067] (2) According to Table 2, the foam slurry prepared in step (1) was injected into the mold, cooled to 30°C at a rate of 3°C / min for solidification, the solidified body was demolded, and placed in a freeze dryer at 60°C to dry to remove water molecules, thereby obtaining a porous piezoelectric ceramic body.
[0068] Table 2 Parameters of Examples 1 to 6
[0069]
[0070] (3) According to Table 3, the porous piezoelectric ceramic body prepared in step (2) was subjected to binder removal, and the binder removal curve was as follows: the temperature was raised to 200°C at a rate of 0.2-0.5°C / min and kept at that temperature for 1-2h, the temperature was further raised to 500°C and kept at that temperature for 1-2h, and the temperature was further raised to 650°C and kept at that temperature for 2-4h.
[0071] Table 3 Parameters of Examples 1 to 6
[0072]
[0073] (4) According to Table 4, the porous piezoelectric ceramic body after debinding in step (3) is sintered at 1200-1300° C. for 2-4 h to obtain a three-dimensional interconnected porous piezoelectric ceramic.
[0074] Table 4 Parameters of Examples 1 to 6
[0075]
[0076] Test Case
[0077] The three-dimensional interconnected porous piezoelectric ceramics prepared in Examples 1 to 6 were subjected to XRD pattern analysis, density and porosity test, and SEM pattern analysis. The density and total porosity were obtained by weighing method, and the open pore porosity was obtained by mercury injection method. At the same time, electrical performance analysis was performed, and the piezoelectric voltage constant d was tested by quasi-static method. 33 and dielectric constant ε r , and thus calculate the piezoelectric voltage constant g33 and piezoelectric energy harvesting factor FOM 33 , using the electromechanical conversion system to test the output electrical performance (peak output voltage V pp and detection sensitivity S), the results are as follows Figures 1 to 6 shown.
[0078] according to Figures 1 to 6 It can be seen that the main phase of the three-dimensional interconnected porous piezoelectric ceramics all show the diffraction peak of the perovskite structure, with a connected three-dimensional skeleton structure and good bonding between grains;
[0079] The density of the three-dimensional interconnected porous piezoelectric ceramic prepared in Example 1 is 0.52 g / cm 3 The total porosity is 93.3%, the open porosity is 91.6%, and the average pore size is 93.2 μm; the piezoelectric charge constant is 431, the dielectric constant is 128, and the piezoelectric voltage constant is 380×10 -3 Vm / N, the energy harvesting factor is 164×10 -12 m 2 / N, peak output voltage V pp It is 140V, and the detection sensitivity is 30V / kPa;
[0080] The density of the three-dimensional interconnected porous piezoelectric ceramic prepared in Example 2 is 0.73 g / cm 3 The total porosity is 90.7%, the open porosity is 88.7%, and the average pore size is 85.5 μm; the piezoelectric charge constant is 455, the dielectric constant is 134, and the piezoelectric voltage constant is 384×10 -3 Vm / N, the energy harvesting factor is 175×10 -12 m 2 / N, peak output voltage V pp It is 155V, and the detection sensitivity is 32V / kPa;
[0081] The density of the three-dimensional interconnected porous piezoelectric ceramic prepared in Example 3 is 0.95 g / cm 3 The total porosity is 87.8%, the open porosity is 85.3%, and the average pore size is 82.41 μm; the piezoelectric charge constant is 465, the dielectric constant is 136, and the piezoelectric voltage constant is 386×10 -3 Vm / N, the energy harvesting factor is 180×10 -12 m 2 / N, peak output voltage V pp It is 172V, and the detection sensitivity is 36V / kPa;
[0082] The density of the three-dimensional interconnected porous piezoelectric ceramic prepared in Example 4 is 1.08 g / cm 3The total porosity is 86.2%, the open porosity is 84.7%, and the average pore size is 80.65 μm; the piezoelectric charge constant is 480, the dielectric constant is 140, and the piezoelectric voltage constant is 387×10 -3 Vm / N, the energy harvesting factor is 186×10 -12 m 2 / N, peak output voltage V pp The voltage is 200V and the detection sensitivity is 40V / kPa;
[0083] The density of the PZNNT porous piezoelectric ceramic prepared in Example 5 is 1.26 g / cm 3 The total porosity is 83.9%, the open porosity is 81.5%, and the average pore size is 79.36 μm; the piezoelectric charge constant is 418, the dielectric constant is 124, and the piezoelectric voltage constant is 381×10 -3 Vm / N, the energy harvesting factor is 159×10 -12 m 2 / N, peak output voltage V pp It is 132V, and the detection sensitivity is 28V / kPa;
[0084] The density of the PZNNT porous piezoelectric ceramic prepared in Example 6 is 1.43 g / cm 3 The total porosity is 81.7%, the open porosity is 79.4%, and the average pore size is 78.65 μm; the piezoelectric charge constant is 400, the dielectric constant is 120, and the piezoelectric voltage constant is 376×10 -3 Vm / N, the energy harvesting factor is 151×10 -12 m 2 / N, peak output voltage V pp The detection voltage is 110V and the detection sensitivity is 25V / kPa.
[0085] It can be seen from the above embodiments that the three-dimensional interconnected porous piezoelectric ceramics provided by the present invention have a lower density and dielectric constant, as well as a higher porosity and piezoelectric charge constant, and are excellent in energy output capacity and sensing sensitivity.
[0086] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A three-dimensional interconnected porous piezoelectric ceramic, characterized in that: The chemical composition is 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3, density is 0.52~1.43g / cm 3 The total porosity is 81.7-93.3%, the open porosity is 79.4-91.6%, the pore size is 10-300 μm, and the average pore size is 78.7-93.2 μm.
2. The three-dimensional interconnected porous piezoelectric ceramic according to claim 1, characterized in that: The pore structure of the three-dimensional interconnected porous piezoelectric ceramic is spherical.
3. The three-dimensional interconnected porous piezoelectric ceramic according to claim 1 or 2, characterized in that: The piezoelectric charge constant d of the three-dimensional interconnected porous piezoelectric ceramic 33 The dielectric constant ε is 400~480pC / N at 1kHz r is 120~140, the piezoelectric voltage constant g 33 376×10 -3 ~387×10 -3 Vm / N, energy harvesting factor FOM 33 151×10 -3 ~186×10 -12 m 2 / N, peak output voltage V pp The detection voltage is 110~200V, and the detection sensitivity is 25~40V / kPa.
4. The method for preparing the three-dimensional interconnected porous piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The following steps are involved: 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 ) After the O3 ceramic slurry, plasticizer, gelling agent and foaming agent are heated and mixed, they are cooled and solidified, freeze-dried, debinded and sintered in sequence to obtain the three-dimensional interconnected porous piezoelectric ceramic.
5. The preparation method according to claim 4, characterized in that: The 0.83Pb(Zr 1 / 2 Ti 1 / 2 )O3-0.11Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.06Pb(Ni 1 / 3 Nb 2 / 3 )O3 ceramic slurry contains PZNNT ceramic powder, the mass ratio of the PZNNT ceramic powder to the plasticizer is 100:3-5; the mass ratio of the PZNNT ceramic powder to the gelling agent is 100:5-8; the mass ratio of the PZNNT ceramic powder to the foaming agent is 100:0.2-1.
2.
6. The preparation method according to claim 4, characterized in that: The cooling and curing process includes cooling and heat preservation, wherein the cooling rate is 2-5°C / min, the final temperature is 25-35°C, and the heat preservation time of the final temperature is 12-36h.
7. The preparation method according to claim 4 or 5, characterized in that: The debinding is performed by gradient heating; the debinding by gradient heating includes sequentially performing a first heating, a first heat preservation debinding, a second heating, a second heat preservation debinding, a third heating and a third heat preservation debinding.
8. The preparation method according to claim 7, characterized in that: The first heating rate is 0.2-0.5°C / min; the first insulation debinding temperature is 150-250°C, and the insulation debinding time is 1-2h; the second heating rate is 0.2-0.5°C / min; the second insulation debinding temperature is 450-550°C, and the insulation debinding time is 1-2h; the third heating rate is 0.2-0.5°C / min; the third insulation debinding temperature is 600-700°C, and the insulation debinding time is 2-4h.
9. The preparation method according to claim 4 or 6, characterized in that: The sintering temperature is 1200-1300° C., and the heat preservation sintering time is 2-4 hours.
10. Use of the three-dimensional interconnected porous piezoelectric ceramic according to any one of claims 1 to 3 or the three-dimensional interconnected porous piezoelectric ceramic obtained by the preparation method according to any one of claims 4 to 9 in a piezoelectric energy harvester.